Immunization with a recombinant antigen composed of conserved blocks from TSA56 provides broad genotype protection against scrub typhus - Kim, Hong-Il (Emerg Microbes Infect, 2019)
Scrub typhus is an acute febrile disease caused by Orientia tsutsugamushi infection. Despite the wide range of approaches explored during the last seventy years, an effective prophylactic vaccine is not yet available. Here, we developed a novel recombinant antigen derived from conserved regions of 56 kDa type-specific antigen (TSA56), a major outer membrane protein responsible for genetic heterogeneity and antigenicity, and evaluated it as a protective vaccine antigen. Our findings demonstrate that immunization with conserved blocks of TSA56 (cTSA56) not only provides protective immunity against lethal challenges with the homologous genotype, but also confers significantly better protection against heterologous genotypes than TSA56. Adoptive transfer of CD4(+) or CD8(+) T cells from immunized mice provided significantly enhanced protection against lethal challenge, whereas immune B cells failed to do so, indicating that cellular immunity against the conserved epitopes plays a protective role. Moreover, immunization with a 10-mer peptide mixture, screened from CD8(+) T cell epitopes within the conserved region of TSA56, provided enhanced protection against lethal challenge with O. tsutsugamushi. Therefore, this novel recombinant antigen is a promising candidate for scrub typhus vaccine against a wide range of O. tsutsugamushi genotypes.